(The Improvement of vetiver Oil (Vetiver zizanoides) Quality by Means of Deterpenation Process) - Moestafa, Achmad; Moermanto, J (Balai Besar Industri Agro, 1988)
Vetiver oil is obtained by distillation. Due to the high cost of production and too small profit margin, farmers tend to reduce the distilling time to a third of its usual practice; e.g. from 36 hours to 12 hours. Young harvested root has also been used now to reduce the cost. All those practices tend to have had influence to the quality of the vetiver oil. Improvements through distillation process and harvesting method seemed need a rather long period. A short cut practice to improve the quality has been carried out by deterpenation process. The result showed that by means of fractional distillation and rejecting the low boiling pint terpenes up to 30% has raised the value of ester number, ester number after acetylation and vetiverol content from 8.17; 119.3 and 46.8% to 13.1; 128.9 and 50.6% respectively.